PhDs, Gospreneurship, Globalization and the Pentecostal ‘new wave’ in Zimbabwe - Marongwe, Ngonidzashe; Maposa, Richard S. (Afro Asian Journal of Social Sciences, 2015)
Researches on Pentecostal Christianity continue to grow in Africa studies. Much of the observation is that Southern Africa, in general and Zimbabwe, in particular has become the stronghold of a bourgeoning new Pentecostal wave today. The study situates this new religious phenomenon in the framework provided by the prophetic healing deliverances (PHDs) in light of the emerging “gospreneurship” and globalization. The paper posits that the Pentecostal Christianity is a response to a deep human crisis in society, whose spirituality calls for a mystical one-on-one relationship with the divine. This spirituality is behind the perceived efficacy of the PHDs that have sustained the miraculous riddles wrought by some of the high profile religious luminaries in contemporary Zimbabwe.
free